Primjena naprednih polimernih materijala - Gilja, Vanja; Katančić, Zvonimir; Kratofil Krehula, Ljerka; Peršić, Ana; Hrnjak-Murgić, Zlata (2019)
Sve intenzivniji razvoj naprednih polimernih materijala kao što su polimerne mješavine i (nano)kompoziti nude brojna inovativna rješenja za različitu upotrebu, što ima velik ekonomski značaj za plastičnu industriju i područja u kojima se primjenjuju. Napredne tehnike modificiranja polimera razvile su se gotovo do krajnjih granica, a znatno su poboljšale omjer troškova i svojstava nastalih modifikacijom strukture polimera. Miješanje različitih polimera, priprema (nano)kompozita te stvaranje višeslojnih materijala, laminata neke su od najznačajnijih tehnika modifikacije. Pri tome postoje sinergistička djelovanja između komponenti, kako bi se postigli izvrsni učinci koji su prilagođeni specifičnim primjenama, kao npr. antimikrobno djelovanje, blokiranje ultraljubičastog svjetla, smanjenje gorivosti, fotokatalitičko djelovanje, a u radu su prikazani rezultati ispitivanja polimernih nanokompozita s ciljem modifikacije navedenih svojstava.
The intense development of advanced polymer materials, such as polymer blends and (nano)composites, offers a number of innovative solutions for different applications, which is of great economic importance for the plastics industry and the fields in which they are applied. Advanced polymer modification techniques have pushed the limit, and have significantly improved the cost/properties ratio engendered by manipulating the structure of polymers. Blending dissimilar polymers, preparing composites where polymer matrix is modified by fillers, and creating multilayer structures and laminates are some of the most significant polymer modification techniques. In such modification, synergistic effects between the components are required in order to achieve excellent performances tailored to specific applications, such as antimicrobial activity, blocking ultraviolet light, reducing flammability, photocatalytic activity. This paper presents the results of the research on polymer nanocomposites aimed at the modification of the aforementioned properties.
Bibliografija: 17 jed.
Sažetak ; Summary.
Keywords: Polimeri -- Polimerni materijali -- Nanokompoziti -- Antimikrobna aktivnost -- Usporivači gorenja -- Fotokatalizatori